Safety and immunogenicity of a quadrivalent, inactivated, split-virion influenza vaccine (IIV4-W) in healthy people aged 3-60 years: a phase III randomized clinical noninferiority trial - Xiaoyuan Huang; Ting Fan; Li Li; Xuanxuan Nian; Jiayou Zhang; Xuefen Gao; Wei Zhao; Wei Chen; Zhaoqing Zhang; Zhihao Yao; Xixin Han; Jinrong Shi; et al. (Taylor & Francis Group, 2022)
Background A quadrivalent split influenza vaccine IIV4-W against both influenza A and B viruses is urgently needed. Methods To evaluate the safety and immunogenicity of IIV4-W in people aged 3-60 years, 2400 participants recruited in a double-blind phase III trial and were randomly assigned to the IIV4-W, TIV1 and TIV2 groups. The immunogenicity indicators were measured at 28 days postvaccination and for 180 days for safety follow-up. Results Adverse events (AEs) occurred in 162 (20.28%), 116 (14.55%) and 123 (15.41%) participants in the IIV4-W, TIV1 and TIV2 groups, respectively. All these AEs were mild and self-limiting, and no serious AEs related to the vaccines were observed. IIV4-W elicited a non-inferior immune response for matched strains (the lower limit of 95% CI for GMT ratio >0.67, for SCR and SPR difference >-10%) and superior immune response for the additional B strains (the lower limit of 95% CI for GMT ratio >1.5, for SCR difference >10%) versus TIVs. The lower limit of the 95% confidence interval of the GMT increase fold, the seroconversion rate and the seroprotection rate exceeded 2.5, 40% and 70% for the four strains in IIV4-W respectively. Conclusions IIV4-W was noninferior to the TIV-matched strains and was superior to the additional B strain. IIV4-W was safe in the participants and elicited high antibody titers.